A Comprehensive Method for Designing Containerized Microgids in Non-Interconnected Zones - Juan Cabrera; Sandra Vasquez-Donado; Cesar Orozco-Henao; Mauricio Restrepo (TESEA, Transactions on Energy Systems and Engineering Applications)
Many isolated rural communities lack basic electricity services and associated modern amenities. One proposed solution is the deployment of containerized microgrids, which are clusters of generation and storage assets packaged in a container for easy deployment. However, few works have described approaches for designing such solutions. This paper presents a five-step method for designing a containerized photovoltaic-based microgrid for isolated areas. The method includes defining system design requirements and constraints (technical, environmental, and legal), conducting preliminary studies on solar radiation and load profiles, selecting equipment, designing the control system, and performing a basic economic analysis. This method is verified in three scenarios of Colombian Non-Interconnected Zones (NIZs), resulting in a solution that can effectively provide electricity to the isolated communities, primarily from solar energy, store surplus generation in batteries, and minimize diesel backup generator use. The results show that the solutions can be scaled to feed larger loads and can be applied in other contexts, such as emergency supply after natural disasters.